Evaluating Indications and Diagnostic Yield of Colonoscopy in Sardjito General Hospital - Suharjo Broto Cahyono; Putut Bayupurnama; Neneng Ratnasari; Catharina Triwikatmani; Fahmi Indrarti; Sutanto Maduseno; Siti Nurdjanah (Faculty of Medicine Universitas Gadjah Mada, 2014)
ABSTRACTBackground: Colonoscopy is the gold standard procedure which is widely used in the diagnosis and treatment of colonic mucosal disorder. Inappropriate colonoscopy indications increase rate of complications.Aim: The main aims of our study were to evaluate indications, fi ndings and diagnostic yield at colonoscopy.Methods: A retrospective study of all colonoscopy was conducted from January 2012 through August 2013, at Dr. Sardjito General Hospital, Yogyakarta and there were 688 colonoscopy reports. Seven colonoscopy indications were documented and presented: rectal bleeding or hematochezia, chronic diarrhea, abdominal pain, constipation, screening and surveillance for colonic neoplasia, change in bowel habit and anemia. Diagnostic yield was defi ned as the ratio between signifi cant fi ndings detected on colonoscopy and the total number of procedures performed for the indication. In our study, diagnostic yield was established by colonoscopy, not confirmed by biopsy.Results: Overall diagnostic yield was 72.53%. The leading indication for colonoscopies was rectal bleeding or hematochezia (36.19%), followed by chronic diarrhea (23.11%), abdominal pain (14.09%), constipation (13.37%), screening and surveillance (5.66%), change in bowel habit (5.52%) and anemia (2.02%). Diagnostic yields according colonoscopies examination were normal (37.14%), colorectal cancer (19.33%), proctitis (14.24%), infl ammatory bowel disease (12.50%), polyps (11.19%),hemorrhoid (10.03%), and diverticel(3.78%). Colorectal cancers were found in patients with hematochezia (74 patients, 29.71%), chronic diarrhea (34 patients, 21.38%), constipation (13 patients, 14.13%). Of 249 patients presenting with hematochezia were found colorectal cancer (74 patients), hemorrhoid (50 patients), proctitis (30 patients), normal (30 patients). Our study showed that diagnostic yield was far lower in patients below 50 years (38.48%) compared > 50 years (61.52%), especially for colorectal cancer (p < 0.001), polyps (p = 0.004) and diverticular (p < 0.001).Conclusions: Hematochezia was the leading indication for colonoscopy and the diagnostic yield was 72.53%. The leading of colonoscopy fi ndings were normal colonoscopies, followed by colorectal cancer, proctitis,infl ammatory bowel disease, polyps and diverticel. Colonoscopy indications should be based on the available guidelines to minimize as much as possible the number inappropriate procedures and complications.Keywords: Colonoscopy, diagnostic yield, colonic indications, appropriateness of colonoscopy